The future of international courts : regional, institutional, and procedural challenges - Kent, Avidan; Skoutaris, Nikos; Trinidad, Jamie (Abingdon, Oxon [UK] ; New York, NY : Routledge, 2019)
The end of World War II marked the beginning of a new golden era in international law. Treaties and international organisations proliferated at an unprecedented rate, and many courts and tribunals were established with a view to ensuring the smooth operation of this new universe of international relations. The network of courts and tribunals that exists today is an important feature of our global society. It serves as an alternative to other, sometimes more violent, forms of dispute settlement. The process of international adjudication is constantly evolving, sometimes in unexpected ways. Through contributions from world-renowned experts and emerging voices, this book considers the future of international courts from a diverse range of perspectives. It examines some of the regional, institutional and procedural challenges that international courts face: the rising influence of powerful states, the turn to populism, the interplay between courts, the involvement of non-state actors and third parties in international proceedings, and more. The book offers a timely discussion of these challenges, with the future of several international courts hanging in the balance and the legitimacy of international adjudication being called constantly into question. It should also serve as a reminder of the importance of international courts for the functioning of a rules-based international order. 'The Future of International Courts' is essential reading for academics, practitioners and students who are interested in international law, including those who are interested in the role international courts play in international relations.
What does the future hold for international courts? -- Critical junctures and the future of international courts in a post-liberal world order -- India and international dispute settlement : some reflections on India's participation in international courts and tribunals -- China's attitude towards international adjudication : past, present and future -- The crisis of the European Court of Human Rights in the face of authoritarian and populist regimes -- Taking back control? Brexit and the court of justice? -- The functions of the International Court of Justice : tending to the law while settling disputes? -- Delegitimation of global courts : lessons from the past -- The future of investor-state dispute settlement -- Learning lessons through the prism of legitimacy : what future for international criminal courts and tribunals? -- How the application of teachings can affect the legitimacy of the International Court of Justice -- Towards separate opinions at the court of justice of the European Union : lessons in deliberative democracy from the International Court of Justice and elsewhere -- From warfare to "lawfare" : increased litigation and rise of parallel proceedings in international courts (a case study of Ukraine's and Georgia's action against the Russian Federation) -- Amicus curiae participation in international proceedings : forever friends? -- Not just a wit, but a cause of wit in others : the influence of human rights in international litigation -- The future of international courts : what next?.
Includes index.
OCLC-licensed vendor bibliographic record.
Keywords: International Court of Justice; European Court of Human Rights; Amicus curiae; International courts; Justice, Administration of; LAW / General; LAW / International